Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T22:20:03+01:00
5-[(8x+7)-18x]=9x
5-(8x+7-18x)-9x=0
5-(-10x+7)-9x=0
5+10x-7-9x=0
x-2=0
x=2

x(2-x)-3x=x[x-(5+2x)]
2x-x^2-3x=x(x-5-2x)
-x^2-x=x^2-5x-2x^2
-x+5x=0
4x=0
x=0
2010-02-28T22:22:36+01:00
Pierwszy przykład:
5 -[(8x+7)-18x]=9x
5-[8X+7-18X]=9X
5-(-10x)+7=9x
5+10x+7=9x
12+10x=9x
12=-10x+9x
-x=12//:-1
x=-12

drugi przykład:
x(2-x) -3x= x [x-(5+2x)]
2x-x2-3x=x[x-5-2x]
-x-x2=x2-5x-2x2
-x+5x=x2+x2+2x2
4x=4x2//:4
x=x2

Mam nadzieję, że ta odpowiedź się przyda:) pozdrawiam